2013
DOI: 10.1016/j.rvsc.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EPA and DHA on lipid droplet accumulation and mRNA abundance of PAT proteins in caprine monocytes

Abstract: a b s t r a c tThe present study investigated the in vitro effects on caprine monocytes of two x-3 PUFAs, namely eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on lipid droplet formation, an emerging process of fundamental importance in innate immunity regulation. The mRNA abundance of PAT protein family (PLIN1, PLIN2 and PLIN3), involved in the formation and trafficking of the droplets, was also assessed. The effects of EPA and DHA on monocyte apoptosis were studied as well. The number of lipid dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
(52 reference statements)
1
14
0
3
Order By: Relevance
“…Since we observed significant dose-dependent increases in TAG and CholE content in response to irradiation and GLA treatment, we analyzed the possible changes in the expression of a lipid binding protein, PLIN3. Perilipins are a multi-protein family that target LD surfaces and regulate lipid storage and hydrolysis [70]. In good accord with the increased TAG content of treated cells, we found that irradiation (both 5 and 10 Gy) significantly induced PLIN3 gene expression in U87 MG cells on incubation for 48 h (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Since we observed significant dose-dependent increases in TAG and CholE content in response to irradiation and GLA treatment, we analyzed the possible changes in the expression of a lipid binding protein, PLIN3. Perilipins are a multi-protein family that target LD surfaces and regulate lipid storage and hydrolysis [70]. In good accord with the increased TAG content of treated cells, we found that irradiation (both 5 and 10 Gy) significantly induced PLIN3 gene expression in U87 MG cells on incubation for 48 h (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…LBs are organelles found in almost all eukaryotic cells, and their number and size vary in different cell types [ 25 , 26 ]. LBs were thought for many years to be storage sites for lipids; now they are beginning to emerge as dynamic organelles and signaling platforms affecting cell fate [ 27 , 28 ]. However the exact role of LBs in neural cell survival and maintenance of neural circuitries is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the analysis of transcriptome goes on, we found two other key genes, PLIN1 and PLIN2, which may have an important regulatory effect on PPAR signaling pathway. PLIN1 and PLIN2 are both the members of PAT protein family which is a key protein that regulates the formation of lipid droplet [ 37 , 38 ]. Previous researches demonstrated that phosphorylated PLIN1 activated lipolytic activity and hydrolysis of triacylglycerides [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%